Benchmarking of a Management System - Jonsson, Henrik (My University, 2008)
This dissertation is a case study from the Swedish nuclear industry, an industry, which is very hard regulated. All proprietors of nuclear facilities in Sweden have to comply with the injunctions of SKI. In injunction SKIFS 2004:1 states SKI (Swedish Nuclear Power Inspectorate) that all nuclear facilities shall be managed and developed with the support of a quality assurance system, they recommend that IAEA’s norms and standards for quality assurance could be used as guidance. In 2006 IAEA released a new set of requirements called IAEA GS-R-3, which focuses on management systems. The Swedish nuclear power plant Ringhals AB wanted to analyse how their management system RVS stood against this standard, this came to be the purpose of this dissertation. Ringhals AB is Sweden’s largest power plant in the Nordic countries and has about 1300 employees. One of the keys within IAEA GS-R-3 is that it integrates all aspects of managing nuclear installations and activities including safety, health, environment, security, quality and economic requirements. It also has strong influences from other management systems standards such as ISO 9001 and ISO 14001. The author has searched through documents within RVS to locate and evaluate if the requirements from the standard are fulfilled. The result from the study was that a few gaps were identified where RVS did not fulfil the requirements in the standards. The requirements that were not fulfilled was further analysed and a suggestions on what RAB can do to fulfil the requirement was given. Apart from direct deviations were also general differences in the approach on management system between IAEA and RAB discussed. The conclusion summons that RVS is a well worked through management system that with some adjustments could fulfil of the requirements in IAEA GS-R-3.
Keywords: Miljöteknik; Environmental engineering